Effects of a 14-day high-intensity shock microcycle in high-level ice hockey players' fitness - Brocherie, F.; Perez, J.; Guilhem, G. (The Journal of Strength and Conditioning Research, 2022)
Elite athletes face congested schedules with increased competition frequency and restricted time for training periods. Therefore, time is lacking to design long-term sport-specific block periodization. This study aimed to investigate the effects of adding a 14-day off-ice high-intensity training (HIT) shock microcycle to the usual training content of the pre-season preparation of high-level male ice hockey players' fitness. Fourteen players were randomly assigned to off-ice HIT (n = 7) or usual pre-season training (control, n = 7). For the HIT group, additional off-ice training content included 2 sessions of repeated-maximal resistance training, 2 sessions of repeated-sprint training, and 2 sessions of high-intensity intermittent training. Control group performed equal number of off-ice sessions using traditional strength and conditioning training. Off-ice Yo-Yo intermittent recovery test level 2 (YYIR2) and on-ice repeated-sprint ability test (RSA) were conducted before (pre-test) and 3 days after the intervention (post-test). Statistical significance was set at p < 0.05. Significant group × time interactions were found for off-ice YYIR2 performance (p < 0.05) and on-ice RSA-cumulated skating time (RSATT; p < 0.05). Compared with pre-test, off-ice YYIR2 distance covered significantly increased (from 708.6 ± 97.2 to 885.7 ± 118.7 m, p < 0.01; +25.8 ± 16.9%, p < 0.05) and on-ice RSATT significantly decreased (from 28.35 ± 0.87 to 28.14 ± 0.84 seconds; -1.7 ± 2.1%, both p < 0.05)] for HIT group. No significant pre-test to post-test changes were found for the control group (+2.7 ± 20.0% for YYIR2 and +0.9 ± 2.2% for RSATT). The implementation of a 14-day shock microcycle (including 6 HIT sessions) significantly improved fitness performance in high-level male ice hockey players. Such HIT block periodization offers a promising way to deal with congested schedules.